The Pros and Cons of the “New Normal” Concept during COVID-19 Outbreak - Nadi Suprapto; Akhmad Zamroni; Azmil Abidah; Desi Wulandari (EDUTEC : Journal of Education And Technology, 2021)
This position paper narrates how the author's position based on the hot issue of nurturing the COVID-19 pandemic. The pros and cons of the "New Normal" concept [kenormalan baru] are argumentatively illustrated through a literature search. The primer information from WHO, policymaker, and researchers contributed to the discussion. Health protocols become the rules mentioned in implementing a new normal, namely by reducing physical contact with others. Nevertheless, the new normal policy is no less low and dangerous, is the insufficient appreciation of science, especially revelation. Thus, the concept of the new normal has not valued except just taking material and economic benefits.